Nutrient acquisition and fruit quality of Ponkan mandarin in response to AMF inoculation - Wu, Qiang-Sheng; GAO, WEI-QIN; Srivastava, A K; Zhang, Fei; Zou, Ying-Ning (The Indian Journal of Agricultural Sciences, 2020)
Arbuscular mycorrhizal fungi (AMF) inhabited in citrus rhizosphere playing multiple roles in plant growth, nutrient acquisition, and stress tolerance are well known under potted conditions. However, information regarding response of AMF application in field citrus trees is scarce. In this study, single inoculation of Funneliformis mosseae and mixture of Diversispora versiformis, F. mosseae, and Rhizoglomus intraradices into the rhizosphere were compared with non-inoculated (control) three-yr-old Citrus reticulata Blanco var. Ponkan cv. Jinshuigan grafted on trifoliate orange grown under open field condition. After eight months of inoculation, root mycorrhiza colonization and soil hyphal length varied respectively from 43% to 56% and from 3.66 to 5.57 cm/g soil and also 1.7-2.2 times and 13.1-19.9 times higher in AM-treated trees than non-inoculated trees. Two AMF treatments collectively increased root P, K, Cu, Zn, and Mn concentrations, sarcocarp P, Mn, and Fe concentrations, peer coloration value, and fruit diameter longitudinal axis, as well as root vitality by 36%-76%. In addition, single F. mosseae inoculation dramatically increased juice soluble solid content and sarcocarp Zn concentrations than non-AMF treatment; mixed-AMF inoculation considerably increased single fruit weight and sarcocarp K and B contents. On the whole, these beneficial effects were superior under mixed AMF treatment than under single AMF treatment. Our study, hence, suggested that mixed culture of AMF inoculation, played an important role in quality production of Pokan mandarin as a viable biofertilizer use option.